Synthesized polymeric nanocomposites with enhanced optical and electrical properties based on gold nanoparticles for optoelectronic applications - Yassin, A. Y. (Journal of materials science. Materials in electronics, 2023)
In the present work, gold nanoparticles (Au-NPs) were synthesized in two ways: plant extract and laser ablation techniques. Then, Au-NPs were added to (PVP/PVA/CMC) blend (TB) to produce novel nanocomposites using the solution casting technique. X-ray diffraction analysis, Ultraviolet and visible spectroscopy, and transmission electron microscopy provided conclusive evidence for preparing Au-NPs through the above methods. The optical, structural, and dielectric properties of the prepared samples were prudently investigated and confirmed their semicrystalline nature. TEM study concluded that Au-NPs are more uniformly distributed in the TB/AuNPs-biosynthesized (TBAu-B) matrix than in the TB/Au-NPs prepared by laser ablation (TBAu-L) matrix. The decrease in interatomic distances increases the refractive index with an enhancement in optical properties. The change in loss tangent provided a deeper discernment into the relaxation dynamics that arose inside the current films. The electric modulus formalism verified the non-Debye behavior of charge carriers inside the TB-based nanocomposite samples. It also demonstrated a remarkable capacitive feature of the nanocomposite films. The dielectric characteristics of the TBAu-B nanocomposite sample have improved, where AC electrical conductivity reached 1.58 × 10 −3 S/cm. Because of this favorable enhancement, the TBAu-B nanocomposite has the potential to be utilized in optoelectronic applications such as sensors.